Aplicación foliar de bioles en el cultivo de cafeto, (Coffea Arabica l.) variedad caturra, en etapa de fructificación en la provincia de el Dorado - Rodriguez Vargas, Tenix (2011)
This thesis entitled "Application bioles leaf in growing coffee (Coffea arabica L.) Variety Caturra in fruiting stage in the Province of El Dorado", was aimed to compare the effect of three sources bioles to guinea pig manure, cattle manure, grass adding treaty (Brizantha) and identify groups of microorganisms in the anaerobic inoculum. The land owned by Mr. Mario Cordova Peña, was located in the jurisdiction of the Commonwealth of Flor Northern District of San Martin de Alao. Province of El Dorado. This study was conducted from 16/11/09 to 03/02/10. We used randomized complete block design with four treatments and four blocks. The foliar treatment were applied in phenological stage of fruit formation. The results indicate that the T1, distinguished by its greater effect on weight variables parchment coffee to 12% moisture, grain yield and coffee tasting it was applied at a rate of 1.5 liters of biol with a frequency of every 15 days in six common applications and was a complement to supply nutrients to the crop that is certainly not replaced at all natural soil nutrition. A determined level of the following fungi genera present in the inoculum, like Penicillium sp. Micogone sp, Fusarium sp, and Sterile. The level of bacteria was determined genres aerobic and anaerobic.